On transient behavior improvement of constrained nonlinear time-delay descriptor systems. (December 2021) - Jafari, E.; Binazadeh, T.
Abstract: This article addresses the control of nonlinear time-delay descriptor systems via Composite Nonlinear Feedback (CNF) control technique to attain both improved transient response and asymptotic output regulation. The suggested CNF controller not only prevails for improving the closed-loop system's transient response, but it is also efficient in overcoming the input saturation constraint and time-delay effects (both constant and time-varying delays). Moreover, the suggested controller is designed under the delay-range dependent condition which causes it to be less conservative than other CNF controllers discussed so far in the literature. The CNF controller's parameters are obtained by solving LMI problems through the given theorems based on the Lyapunov approach to stability analysis. The theoretical achievements are admitted by computer simulation of some illustrative examples. Highlights: Proposing a CNF controller for descriptor nonlinear time-delay systems. Considering two main types of time-delays i.e. constant and time-varying delays. Guaranteeing the performance in the presence of multiple delays. Providing stability conditions as LMI problems. Endorsing the theoretical results through computer simulations.